Long-acting saline-alkaline-tolerant concrete internal curing material and preparation method thereof

By using composites prepared by nano-calcium carbonate, eloite, sodium humate and other components, combined with crosslinking agent and graft polymerization, the problem of poor durability of existing internal health materials in saline-alkali environments is solved, and the long-term internal health and mechanical properties of concrete are improved.

CN119797810AActive Publication Date: 2025-04-11XIAN UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510022768.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

Existing polymer internal health materials have poor durability in saline-alkali environments, which can easily weaken the concrete performance and internal curing efficiency due to premature release of moisture.

Method used

Organized nano calcium carbonate-sodium humate-eloite composites are prepared using components such as nano calcium carbonate, eloite, and sodium humate, and through crosslinking agent and graft polymerization, a long-acting saline-alkali-resistant concrete internal health material is formed.

Benefits of technology

It significantly improves the compressive strength and mechanical properties of concrete, extends the service life of concrete, reduces maintenance costs, and maintains good absorption-storage properties in a saline-alkali environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a long-acting saline-alkaline-tolerant concrete internal curing material and a preparation method thereof, and belongs to the technical field of building materials. The material is prepared from the following raw materials in percentage by weight: 12%-17% of nano calcium carbonate, 3%-5% of halloysite, 10%-12% of sodium humate, 6%-8% of 3-aminopropyltriethoxysilane, 5%-10% of sodium carboxymethyl cellulose, 3%-4% of lambda-type carrageenan, 1%-2% of locust bean gum, 1%-1.8% of slaked lime, 26%-30% of first part N-hydroxymethyl acrylamide and 20%-23% of hydroxyethyl methylacrylate, the first part of N-hydroxymethyl acrylamide, 5-8% of methacrylic acid, 0.2-0.3% of aluminum oxide, 0.2-0.5% of second part of N-hydroxymethyl acrylamide and 0.5-1% of ammonium sulfite. The material not only has saline-alkaline tolerance, but also can significantly reduce concrete shrinkage and improve mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a long-acting salt-alkali resistant concrete curing material and a preparation method thereof. Background Art

[0002] Infrastructure construction is closely related to concrete engineering construction. Civil engineering construction in some special environmental areas requires the preparation of concrete that meets the performance requirements according to local environmental characteristics. Otherwise, it is very easy for environmental factors to cause varying degrees of damage to concrete. Especially in some plateau areas, climates such as strong winds, dryness, and large temperature differences will have an adverse effect on concrete construction, hydration, and maintenance. In addition, plateau areas often have abundant salt lake resources, which makes the water quality in many high-altitude areas weakly alkaline, with high mineral content and high hardness. This high-altitude and complex water quality environment condition interacts with strong corrosive ions, causing the local cement concrete to crack and damage at a much higher rate than inland areas. Concrete is also more likely to crack and loosen during service, causing durability problems such as leakage and freeze-thaw damage to the structure.

[0003] In recent years, internal curing has become the most effective means of concrete maintenance, and it is also one of the most effective methods to alleviate concrete self-drying and shrinkage cracking. At the same time, this method is simple in process and easy to operate. It can eliminate processes such as film covering, demolding, and repeated watering without adding equipment and process links, and replace traditional curing processes such as watering, spraying, water enclosure, covering, and film covering, thereby improving construction efficiency. It is especially suitable for large-scale concrete construction in certain high-altitude cold areas. The polymer internal curing materials in the internal curing materials currently have a more significant internal curing effect. They are mainly based on acrylic acid, acrylamide, etc. as monomers, and use their own hydroxyl groups, carboxyl groups, etc., and their three-dimensional network structure and the hydrophilicity of the group to absorb moisture. These adsorbed water can be easily released according to the needs of hydration, or replenish the water lost due to evaporation or self-drying, thereby improving the hydration degree of cementitious materials such as cement and alleviating the shrinkage deformation of concrete.

[0004] However, the polymer internal curing materials commonly used in concrete are mostly acrylic acid and acrylic acid salt polymers, which have poor salt and alkali resistance and low liquid absorption rate in alkaline solution and salt solution. Therefore, in the current application of polymer internal curing materials in the field of construction engineering, there is a lack of scientific design ideas for the synthesis and development of polymer internal curing materials, and concrete internal curing materials with good adaptability have not been developed. Most of the existing preparations of polymer internal curing materials are focused on synthesis and modification for the purpose of improving water absorption rate, and few molecular structure designs are carried out based on the alkaline environment inside the concrete mixture and the application environment. Especially when applied to certain saline-alkali environment areas, it is very easy to release the pre-absorbed water prematurely, causing concrete bleeding, thereby weakening the performance of the concrete and the internal curing efficiency. Summary of the invention

[0005] In order to overcome the problems existing in the concrete curing process under saline-alkali environment in the above-mentioned prior art, the purpose of the present invention is to provide a long-term salt-alkali resistant concrete curing material and a preparation method thereof, which material not only has salt-alkali resistance, but also can significantly reduce concrete shrinkage and improve mechanical properties, so as to ensure the long-term concrete curing efficiency caused by climatic characteristics such as strong winds, dryness, and large temperature differences in some areas, so that the curing material maintains good absorption-storage moisture characteristics in a saline-alkali environment, thereby controlling the drying shrinkage and early temperature shrinkage of concrete in the area, reducing the generation of concrete microcracks, improving the mechanical properties and service life of concrete materials, and reducing maintenance costs.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention provides a long-acting salt-alkali resistant concrete curing material, which is prepared from the following raw materials by weight: 12% to 17% of nano calcium carbonate, 3% to 5% of halloysite, 10% to 12% of sodium humate, 6% to 8% of 3-aminopropyltriethoxysilane, 5% to 10% of sodium carboxymethyl cellulose, 3% to 4% of lambda carrageenan, 1% to 2% of locust bean gum, 1% to 1.8% of slaked lime, 26% to 30% of a first portion of N-hydroxymethyl acrylamide, 20% to 23% of hydroxyethyl methacrylate, 5% to 8% of methacrylic acid, 0.2% to 0.3% of aluminum oxide, 0.2% to 0.5% of a second portion of N-hydroxymethyl acrylamide, and 0.5% to 1% of ammonium sulfite.

[0008] In one embodiment, the nano calcium carbonate has a particle size of 15 to 40 nm, a calcium carbonate content of ≥98.5, a pH of 8.5 to 10, and an impurity content of <0.1%;

[0009] The particle diameter of halloysite is 0.1-0.4 μm, the length is less than 0.5 μm, and the purity is ≥99%;

[0010] The particle diameter of the sodium humate is 120 meshes, the sodium humate content (dry basis) is ≥85%, the water-insoluble matter content is <5%, the pH is 9-11, and the moisture content is <12%.

[0011] In one embodiment, the sodium carboxymethyl cellulose is food grade and has a degree of substitution of ≥0.9.

[0012] In one embodiment, the nano-calcium carbonate, halloysite, sodium humate, and 3-aminopropyltriethoxysilane are used to prepare an organic nano-calcium carbonate-sodium humate-haloysite composite;

[0013] The organic nano calcium carbonate-sodium humate-halloysite composite is prepared by the following process:

[0014] Nano-calcium carbonate and halloysite are mixed with deionized water to prepare nano-calcium carbonate suspension A with a weight percentage of 2% and halloysite suspension B with a weight percentage of 1% respectively;

[0015] 3-aminopropyltriethoxysilane is prepared into a 3-aminopropyltriethoxysilane dilute solution with a mass concentration of 3%, and acetic acid is added to adjust the pH to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0016] Nano calcium carbonate suspension A and halloysite suspension B are uniformly dispersed in 3-aminopropyltriethoxysilane hydrolyzate C in sequence, heated in a water bath, stirred, sodium humate is added, stirred continuously, cooled, filtered, washed, dried and ground to obtain an organic nano calcium carbonate-sodium humate-halloysite complex.

[0017] In one embodiment, the acetic acid adjusts the pH to 5.5-6.

[0018] The present invention also provides a method for preparing a long-acting salt-alkali resistant concrete curing material, comprising the following steps:

[0019] An organic nano calcium carbonate-sodium humate-halloysite composite was prepared by using nano calcium carbonate, halloysite, sodium humate and 3-aminopropyltriethoxysilane, which was recorded as composite D. Then, composite D was added with water to prepare suspension E.

[0020] Dispersing λ carrageenan and locust bean gum in deionized water in sequence to prepare a dilute solution F;

[0021] Add deionized water to methacrylic acid to prepare a dilute methacrylic acid solution, add slaked lime and cool to room temperature, and add the first portion of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate during stirring to obtain a mixture G;

[0022] Stirring sorbitan monostearate and cyclohexane in a constant temperature water bath to form an oil phase;

[0023] Adding a suspension E of an organized nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, stirring continuously, adding sodium carboxymethyl cellulose, λ-carrageenan and a dilute solution F of locust bean gum in sequence during stirring, and adding ammonium sulfite after a set time to obtain a mixed solution H;

[0024] The mixture G is added dropwise to the mixture H, and after the addition is completed, aluminum oxide and a second portion of N-hydroxymethyl acrylamide are added to react to obtain a complex I;

[0025] The composite I is taken out, soaked and cleaned to obtain the long-acting salt-alkali resistant concrete curing material.

[0026] In one embodiment, the weight percentage of the suspension E is 2%; the mass concentration of the dilute solution F is 1%; and the mass concentration of the dilute methacrylic acid solution is 15%.

[0027] In one embodiment, the sorbitan monostearate and cyclohexane are stirred at 250 r / min for 30 min in a constant temperature water bath environment at 30° C. to 35° C. to form an oil phase;

[0028] The mass fraction of sorbitan monostearate is 5% to 7% of cyclohexane, and the volume ratio of the oil phase to the water phase is 4 to 4.5:1.

[0029] In one embodiment, the specific process of preparing the mixed solution H is as follows:

[0030] The suspension E of the organic nano-calcium carbonate-sodium humate-halloysite complex was slowly added to the oil phase, nitrogen was passed through, and the mixture was stirred at a speed of 300 r / min for 20 min in a constant temperature water bath environment of 35°C. During the continuous stirring process, the weighed sodium carboxymethyl cellulose and the pre-mixed λ-type carrageenan and locust bean gum dilute solution F were added in sequence, and the mixture was stirred at a speed of 450 r / min. After a setting time of 15 min, ammonium sulfite was added, and the mixture was stirred for 20 min to obtain a mixed solution H.

[0031] In one embodiment, the specific preparation process of the complex I is as follows:

[0032] The mixture G is slowly added dropwise to the mixed solution H for 2 to 3 hours. After the addition is completed, aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, complex I is obtained.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention provides a long-term salt-alkali resistant concrete curing material. First, the material contains nano calcium carbonate components. The particle size of the nano calcium carbonate is 15 to 40 nm, which has a large specific surface area and has a more significant effect on the mechanical properties of concrete. The addition of nano calcium carbonate can enhance the compressive strength, flexural strength, bonding strength, fracture performance, splitting tensile strength, microhardness and elastic modulus of concrete. Used as an auxiliary material and filling material for the rigid skeleton of the internal curing material, it can significantly improve the hardness and water retention of the internal curing gel, and increase the interfacial bonding strength between the internal curing material and the concrete material, thereby having a certain auxiliary effect in resisting shrinkage, bending, deformation and fracture during the concrete curing process. In addition, nano calcium carbonate can significantly enhance the salt and alkali resistance of the internal curing material, ensuring that the internal curing material maintains good water absorption and storage characteristics in the alkaline environment of concrete.

[0035] Secondly, the material contains halloysite, which is an aluminosilicate compound with high porosity and large specific surface area. It can provide the initial three-dimensional skeleton of the long-term salt-alkali resistant internal curing material, and the large number of internal pores also provide attachment points for organic monomers in the polymerization process; and the halloysite crystal layer contains a large number of hydroxyl groups, which can react with olefin monomers to form polymer gels. In addition, the composite between inorganic materials and organic monomers increases the three-dimensional network density of the internal curing material, so that the long-term salt-alkali resistant concrete internal curing material formed after completion exhibits good water retention performance. The slow release of water inside the internal curing material replenishes the water consumption of the concrete, controls and reduces the shrinkage of the concrete, and ensures that the concrete material is fully hydrated; in addition, a certain amount of halloysite dispersed in the internal curing material has a certain auxiliary effect on reducing volume deformation during the internal curing process of concrete.

[0036] Finally, the sodium humate in the material contains a large number of hydroxyl groups in its structure, which can provide an initial organic three-dimensional skeleton of a long-term salt-alkali resistant internal curing material. Free radicals are generated under the action of an initiator, and organic monomers can copolymerize at this position. N-hydroxymethyl acrylamide and hydroxyethyl methacrylate are both non-ionic monomers, and their copolymers exhibit good salt-alkali resistance. They are continuously grafted and polymerized with sodium carboxymethyl cellulose, λ-type carrageenan and locust bean gum, and the nano-calcium carbonate-sodium humate-halloysite composite is continuously filled, which can significantly improve the liquid absorption rate of the curing material. In addition, the relatively excellent salt and alkali resistance can more effectively adjust the humidity distribution inside the concrete to a certain extent, and ensure the internal curing efficiency of the internal curing material in the alkaline environment of the concrete and other saline-alkali media. Therefore, the salt-alkali resistant concrete internal curing material prepared by the present invention has a great contribution to the shrinkage, durability and service life of the concrete internal curing process under saline-alkali environment. DETAILED DESCRIPTION

[0037] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0038] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0039] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0040] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0041] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0042] The invention provides a long-acting salt-alkali resistant concrete curing material and a preparation method thereof.

[0043] On the one hand, the present invention provides a method for preparing a long-term salt-alkali resistant concrete curing material, which is composed of the following raw materials: nano calcium carbonate, sodium humate, halloysite, 3-aminopropyltriethoxysilane and acetic acid, a first portion of N-hydroxymethyl acrylamide, hydroxyethyl methacrylate, methacrylic acid, sodium carboxymethyl cellulose, λ-type carrageenan, locust bean gum, sorbitan monostearate (Span 60), cyclohexane, ammonium sulfite, aluminum oxide, a second portion of N-hydroxymethyl acrylamide, isopropyl alcohol, and slaked lime.

[0044] The nano calcium carbonate, sodium humate, halloysite, 3-aminopropyltriethoxysilane and acetic acid are used to prepare an organic nano calcium carbonate-sodium humate-haloysite composite.

[0045] Calculated by weight, the long-term salt-alkali resistant concrete curing material is composed of the following raw materials: 12% to 17% nano calcium carbonate, 3% to 5% halloysite, 10% to 12% sodium humate, 6% to 8% 3-aminopropyltriethoxysilane, 5% to 10% sodium carboxymethyl cellulose, 3% to 4% lambda carrageenan, 1% to 2% locust bean gum, 1% to 1.8% slaked lime, 26% to 30% of the first part of N-hydroxymethyl acrylamide, 20% to 23% of hydroxyethyl methacrylate, 5% to 8% of methacrylic acid, 0.2% to 0.3% alumina, 0.2% to 0.5% of the second part of N-hydroxymethyl acrylamide, and 0.5% to 1% of ammonium sulfite.

[0046] The organic nano calcium carbonate-sodium humate-halloysite composite is prepared from the following raw materials: nano calcium carbonate, sodium humate, halloysite, 3-aminopropyltriethoxysilane and acetic acid.

[0047] The preparation process of the above-mentioned organic nano calcium carbonate-sodium humate-halloysite composite is as follows:

[0048] Step 1: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse for 30 minutes to obtain a nano-calcium carbonate suspension A and a halloysite suspension B;

[0049] Step 2: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0050] Step 3: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed, the mixed solution is heated to 45°C in a water bath, and constant temperature magnetic stirring is performed for 1 hour, the weighed sodium humate is added, and constant temperature magnetic stirring is continued for 3 hours, and then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, and dried in a vacuum oven at 60°C for 12 hours and then ground to obtain an organic nano calcium carbonate-sodium humate-halloysite complex.

[0051] Among them, the particle size of nano calcium carbonate powder is 15-40nm, the calcium carbonate content is ≥98.5, the pH is 8.5-10, and the impurity content is <0.1%. Nano calcium carbonate is a white fine crystalline powder. It is a cheap natural inorganic material that is insensitive to salt and alkali ions. It is extremely abundant in nature. Introducing nano calcium carbonate into the internal health-care material can improve the salt resistance and compression resistance of the internal health-care material. The introduction of nano calcium carbonate can also reduce the preparation cost of the internal health-care material. In addition, nano calcium carbonate can play a micro-aggregate effect, a crystal nucleus effect, and a filling effect in concrete. A small amount of nano calcium carbonate can promote the hydration of cement to a certain extent. As a filler in cement, it has good performance, can improve the bending and compressive strength of concrete, accelerate the hydration rate of calcium silicate, and make the microstructure of concrete more compact.

[0052] The diameter of the Halloysite powder particles is 0.1-0.4 μm, the length is less than 0.5 μm, and the purity is ≥99%. Halloysite is an aluminum silicate compound with high porosity, large volume, light weight, low bulk density, and large specific surface area. Its crystal layer contains a large number of hydroxyl groups, which can react with olefin monomers to form polymer gels. In this application, it is used as an auxiliary material and filling material for the rigid skeleton of the internal health-promoting material.

[0053] The diameter of the sodium humate particles is 120 meshes, the sodium humate content (dry basis) is ≥85%, the water-insoluble matter content is <5%, the pH is 9-11, and the moisture content is <12%.

[0054] Among them, sodium carboxymethyl cellulose is food grade, with a degree of substitution (DS) ≥ 0.9. Sodium carboxymethyl cellulose is a white to light yellow powder, and its three-dimensional structure contains a large number of hydrophilic groups such as hydroxyl and carboxyl. It has strong water absorption, is easily soluble in water, and exhibits good salt resistance.

[0055] Among them, λ carrageenan is a white powder, which is soluble in hot water at about 80°C to form a viscous, transparent or slightly milky, easy-flowing solution. Its performance is less affected by salt and alkali, and can be used for the synthesis of endo-health materials to improve the elasticity and water retention of endo-health materials.

[0056] Among them, the molecular formula of hydroxyethyl methacrylate is C6H 10 O3 is a colorless, transparent, easy-flowing liquid, soluble in common organic solvents and miscible with water. It is mainly used for the modification of resins and coatings. It can be copolymerized with other acrylic monomers to produce acrylic resins with active hydroxyl groups in the side chains. It can undergo esterification and cross-linking reactions and is used as an important monomer for the synthesis of endogenous health-preserving materials.

[0057] Another aspect of the present invention provides a method for preparing a long-acting salt-alkali resistant concrete internal curing material, the method adopts the above-mentioned formula for preparing the long-acting salt-alkali resistant concrete internal curing material, and the method is carried out according to the following steps:

[0058] Step 1: Weigh the above raw materials by mass;

[0059] Step 2: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse them for 30 minutes to obtain a nano-calcium carbonate suspension A and a halloysite suspension B;

[0060] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a 3% 3-aminopropyltriethoxysilane dilute solution, and then acetic acid is added and adjusted to pH = 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0061] Step 4: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed, the mixed solution is heated to 45° C. in a water bath, and magnetically stirred at a constant temperature for 1 hour, the weighed sodium humate is added, and the magnetic stirring at a constant temperature is continued for 3 hours, and then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, and dried in a vacuum oven at 60° C. for 12 hours and then ground to obtain an organic nano calcium carbonate-sodium humate-haloysite complex, which is recorded as complex D, and then water is added to the complex D to prepare a suspension E with a weight percentage of 2%;

[0062] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a mass concentration of 1%;

[0063] Step 6: Add methacrylic acid to deionized water to prepare a dilute solution with a mass concentration of 15%, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0064] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0065] Step 8: slowly add the suspension E of the pre-obtained organic nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35°C, add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0066] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0067] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0068] Wherein, in step seven, the sorbitan monostearate (Span 60) and cyclohexane are fully mixed to form an oil phase, the sorbitan monostearate (Span 60) is 5% to 7% of the mass fraction of cyclohexane, the volume ratio of the oil phase to the water phase is 4 to 4.5:1, and the water phase is specifically composed of a suspension E (a suspension of an organic nano-calcium carbonate-sodium humate-halloysite complex), a mixed solution F (an aqueous solution of λ-type carrageenan and locust bean gum), and a mixed solution G (a mixture of a dilute methacrylic acid solution, slaked lime, N-hydroxymethyl acrylamide and hydroxyethyl methacrylate).

[0069] The present invention firstly uses 3-aminopropyl triethoxysilane to carry out organic modification on an inorganic powder material with good salt and alkali resistance, and prepares a suspension thereof, then adds N-hydroxymethyl acrylamide, hydroxyethyl methacrylate and methacrylic acid solution, and continuously carries out graft polymerization in an organic nano calcium carbonate-sodium humate-halloysite composite under the action of a crosslinking agent aluminum oxide and N-hydroxymethyl acrylamide, and fills the composite, and after the reaction is completed, the product is dehydrated, dried and screened by isopropanol to obtain the long-acting salt and alkali resistant internal health-preserving water-retaining material. The salt and alkali resistance of the long-acting salt and alkali resistant internal health-preserving material prepared by the present invention is improved, and the compressive strength of the concrete is significantly improved, and the 28d compressive strength of the concrete is more than 120% of the strength of the benchmark concrete, and the self-shrinkage of the concrete can also be greatly reduced.

[0070] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0071] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0072] Embodiment 1:

[0073] This example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 12% nano calcium carbonate, 3% halloysite, 10% sodium humate, 6% 3-aminopropyltriethoxysilane, 5% sodium carboxymethyl cellulose, 3% λ carrageenan, 1% locust bean gum, 1.7% slaked lime, 30% first part N-hydroxymethyl acrylamide, 20% hydroxyethyl methacrylate, 7% methacrylic acid, 0.3% aluminum oxide, 0.5% second part N-hydroxymethyl acrylamide, and 0.5% ammonium sulfite.

[0074] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0075] Step 1: Weigh the above raw materials by mass;

[0076] Step 2: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse them for 30 minutes to obtain suspension A and suspension B;

[0077] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0078] Step 4: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed, the mixed solution is heated to 45° C. in a water bath, and magnetically stirred at a constant temperature for 1 hour, the weighed sodium humate is added, and the magnetic stirring at a constant temperature is continued for 3 hours, and then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, and dried in a vacuum oven at 60° C. for 12 hours and then ground to obtain an organic nano calcium carbonate-sodium humate-haloysite complex, which is recorded as complex D, and then water is added to the complex D to prepare a suspension E with a weight percentage of 2%;

[0079] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0080] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0081] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0082] Step 8: slowly add the suspension E of the pre-obtained organic nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35°C, add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0083] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0084] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0085] Embodiment 2:

[0086] This example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 17% nano calcium carbonate, 3% halloysite, 10% sodium humate, 6% 3-aminopropyltriethoxysilane, 5% sodium carboxymethyl cellulose, 3% λ carrageenan, 2% locust bean gum, 1.2% slaked lime, 26% first part N-hydroxymethyl acrylamide, 20% hydroxyethyl methacrylate, 5% methacrylic acid, 0.3% aluminum oxide, 0.5% second part N-hydroxymethyl acrylamide, and 1% ammonium sulfite.

[0087] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0088] Step 1: Weigh the above raw materials by mass;

[0089] Step 2: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse them for 30 minutes to obtain suspension A and suspension B;

[0090] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0091] Step 4: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed, the mixed solution is heated to 45° C. in a water bath, and magnetically stirred at a constant temperature for 1 hour, the weighed sodium humate is added, and the magnetic stirring at a constant temperature is continued for 3 hours, and then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, and dried in a vacuum oven at 60° C. for 12 hours and then ground to obtain an organic nano calcium carbonate-sodium humate-haloysite complex, which is recorded as complex D, and then water is added to the complex D to prepare a suspension E with a weight percentage of 2%;

[0092] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0093] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0094] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0095] Step 8: slowly add the suspension E of the pre-obtained organic nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35°C, add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0096] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0097] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0098] Embodiment 3:

[0099] This example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 12% nano calcium carbonate, 3% halloysite, 10% sodium humate, 6% 3-aminopropyltriethoxysilane, 6% sodium carboxymethyl cellulose, 4% λ carrageenan, 2% locust bean gum, 1.2% slaked lime, 26% first part N-hydroxymethyl acrylamide, 23% hydroxyethyl methacrylate, 5% methacrylic acid, 0.3% aluminum oxide, 0.5% second part N-hydroxymethyl acrylamide, and 1% ammonium sulfite.

[0100] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0101] Step 1: Weigh the above raw materials by mass;

[0102] Step 2: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse them for 30 minutes to obtain suspension A and suspension B;

[0103] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0104] Step 4: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed, the mixed solution is heated to 45° C. in a water bath, and magnetically stirred at a constant temperature for 1 hour, the weighed sodium humate is added, and the magnetic stirring at a constant temperature is continued for 3 hours, and then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, and dried in a vacuum oven at 60° C. for 12 hours and then ground to obtain an organic nano calcium carbonate-sodium humate-haloysite complex, which is recorded as complex D, and then water is added to the complex D to prepare a suspension E with a weight percentage of 2%;

[0105] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0106] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0107] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0108] Step 8: slowly add the suspension E of the pre-obtained organic nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35°C, add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0109] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0110] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0111] Embodiment 4:

[0112] This example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 12% nano calcium carbonate, 3% halloysite, 10% sodium humate, 6% 3-aminopropyltriethoxysilane, 5% sodium carboxymethyl cellulose, 3% λ carrageenan, 1% locust bean gum, 1% slaked lime, 27% first part N-hydroxymethyl acrylamide, 23% hydroxyethyl methacrylate, 8% methacrylic acid, 0.3% aluminum oxide, 0.2% second part N-hydroxymethyl acrylamide, and 0.5% ammonium sulfite.

[0113] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0114] Step 1: Weigh the above raw materials by mass;

[0115] Step 2: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse them for 30 minutes to obtain suspension A and suspension B;

[0116] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0117] Step 4: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed, the mixed solution is heated to 45° C. in a water bath, and magnetically stirred at a constant temperature for 1 hour, the weighed sodium humate is added, and the magnetic stirring at a constant temperature is continued for 3 hours, and then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, and dried in a vacuum oven at 60° C. for 12 hours and then ground to obtain an organic nano calcium carbonate-sodium humate-haloysite complex, which is recorded as complex D, and then water is added to the complex D to prepare a suspension E with a weight percentage of 2%;

[0118] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0119] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0120] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0121] Step 8: slowly add the suspension E of the pre-obtained organic nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35°C, add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0122] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0123] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0124] Embodiment 5:

[0125] This example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 13% nano calcium carbonate, 4% halloysite, 10% sodium humate, 7% 3-aminopropyltriethoxysilane, 5% sodium carboxymethyl cellulose, 3% λ carrageenan, 1% locust bean gum, 1% slaked lime, 28% first part N-hydroxymethyl acrylamide, 21% hydroxyethyl methacrylate, 6% methacrylic acid, 0.2% aluminum oxide, 0.3% second part N-hydroxymethyl acrylamide, and 0.5% ammonium sulfite.

[0126] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0127] Step 1: Weigh the above raw materials by mass;

[0128] Step 2: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse them for 30 minutes to obtain suspension A and suspension B;

[0129] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0130] Step 4: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed, the mixed solution is heated to 45° C. in a water bath, and magnetically stirred at a constant temperature for 1 hour, the weighed sodium humate is added, and the magnetic stirring at a constant temperature is continued for 3 hours, and then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, and dried in a vacuum oven at 60° C. for 12 hours and then ground to obtain an organic nano calcium carbonate-sodium humate-haloysite complex, which is recorded as complex D, and then water is added to the complex D to prepare a suspension E with a weight percentage of 2%;

[0131] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0132] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0133] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0134] Step 8: slowly add the suspension E of the pre-obtained organic nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35°C, add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0135] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0136] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0137] Embodiment 6:

[0138] This example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 12.7% nano calcium carbonate, 5% halloysite, 10% sodium humate, 6% 3-aminopropyltriethoxysilane, 5% sodium carboxymethyl cellulose, 3% λ carrageenan, 1.5% locust bean gum, 1.8% slaked lime, 27% first part N-hydroxymethyl acrylamide, 22% hydroxyethyl methacrylate, 5% methacrylic acid, 0.3% aluminum oxide, 0.2% second part N-hydroxymethyl acrylamide, and 0.5% ammonium sulfite.

[0139] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0140] Step 1: Weigh the above raw materials by mass;

[0141] Step 2: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse them for 30 minutes to obtain suspension A and suspension B;

[0142] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0143] Step 4: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed, the mixed solution is heated to 45° C. in a water bath, and magnetically stirred at a constant temperature for 1 hour, the weighed sodium humate is added, and the magnetic stirring at a constant temperature is continued for 3 hours, and then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, and dried in a vacuum oven at 60° C. for 12 hours and then ground to obtain an organic nano calcium carbonate-sodium humate-haloysite complex, which is recorded as complex D, and then water is added to the complex D to prepare a suspension E with a weight percentage of 2%;

[0144] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0145] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0146] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0147] Step 8: slowly add the suspension E of the pre-obtained organic nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35°C, add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0148] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0149] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0150] Embodiment 7:

[0151] This example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 12% nano calcium carbonate, 3% halloysite, 12% sodium humate, 8% 3-aminopropyltriethoxysilane, 5% sodium carboxymethyl cellulose, 3% λ carrageenan, 1% locust bean gum, 1.4% slaked lime, 26% first part N-hydroxymethyl acrylamide, 20% hydroxyethyl methacrylate, 7% methacrylic acid, 0.3% aluminum oxide, 0.4% second part N-hydroxymethyl acrylamide, and 0.9% ammonium sulfite.

[0152] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0153] Step 1: Weigh the above raw materials by mass;

[0154] Step 2: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse them for 30 minutes to obtain suspension A and suspension B;

[0155] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0156] Step 4: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed, the mixed solution is heated to 45° C. in a water bath, and magnetically stirred at a constant temperature for 1 hour, the weighed sodium humate is added, and the magnetic stirring at a constant temperature is continued for 3 hours, and then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, and dried in a vacuum oven at 60° C. for 12 hours and then ground to obtain an organic nano calcium carbonate-sodium humate-haloysite complex, which is recorded as complex D, and then water is added to the complex D to prepare a suspension E with a weight percentage of 2%;

[0157] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0158] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0159] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0160] Step 8: slowly add the suspension E of the pre-obtained organic nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35°C, add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0161] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0162] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0163] Embodiment 8:

[0164] This example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 12% nano calcium carbonate, 3% halloysite, 10% sodium humate, 6% 3-aminopropyltriethoxysilane, 10% sodium carboxymethyl cellulose, 3% lambda carrageenan, 1% locust bean gum, 1% slaked lime, 26% first part N-hydroxymethyl acrylamide, 20% hydroxyethyl methacrylate, 7% methacrylic acid, 0.2% alumina, 0.2% second part N-hydroxymethyl acrylamide, and 0.6% ammonium sulfite.

[0165] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0166] Step 1: Weigh the above raw materials by mass;

[0167] Step 2: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse them for 30 minutes to obtain suspension A and suspension B;

[0168] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0169] Step 4: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed, the mixed solution is heated to 45° C. in a water bath, and magnetically stirred at a constant temperature for 1 hour, the weighed sodium humate is added, and the magnetic stirring at a constant temperature is continued for 3 hours, and then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, and dried in a vacuum oven at 60° C. for 12 hours and then ground to obtain an organic nano calcium carbonate-sodium humate-haloysite complex, which is recorded as complex D, and then water is added to the complex D to prepare a suspension E with a weight percentage of 2%;

[0170] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0171] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0172] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0173] Step 8: slowly add the suspension E of the pre-obtained organic nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35°C, add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0174] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0175] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0176] Comparative Example 1

[0177] This comparative example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 5% halloysite, 12% sodium humate, 8% 3-aminopropyltriethoxysilane, 10% sodium carboxymethyl cellulose, 4% λ carrageenan, 2% locust bean gum, 1% slaked lime, 30% first part N-hydroxymethyl acrylamide, 20% hydroxyethyl methacrylate, 7% methacrylic acid, 0.3% aluminum oxide, 0.2% second part N-hydroxymethyl acrylamide, and 0.5% ammonium sulfite.

[0178] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0179] Step 1: Weigh the above raw materials by mass;

[0180] Step 2: Weigh the halloysite and deionized water to prepare a 1% by weight halloysite suspension, and ultrasonically disperse it for 30 minutes to obtain a suspension B;

[0181] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0182] Step 4: uniformly disperse the halloysite suspension B in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2, pass argon, heat the mixture in a water bath to 45° C., and stir it with a constant temperature magnetic force for 1 hour, add the weighed sodium humate, continue to stir it with a constant temperature magnetic force for 3 hours, then cool the mixture to room temperature, filter it, wash the filter cake with distilled water, dry it in a vacuum oven at 60° C. for 12 hours, and then grind it to obtain an organic sodium humate-halloysite complex, recorded as complex D, and then add water to the complex D to prepare a suspension E with a weight percentage of 2%;

[0183] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0184] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0185] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0186] Step 8: slowly add the suspension E of the pre-obtained organic sodium humate-halloysite complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35° C., add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0187] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0188] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0189] Comparative Example 2

[0190] This comparative example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 17% nano calcium carbonate, 10% sodium humate, 8% 3-aminopropyltriethoxysilane, 5% sodium carboxymethyl cellulose, 4% λ carrageenan, 2% locust bean gum, 1% slaked lime, 26% first part N-hydroxymethyl acrylamide, 20% hydroxyethyl methacrylate, 6% methacrylic acid, 0.3% aluminum oxide, 0.2% second part N-hydroxymethyl acrylamide, and 0.5% ammonium sulfite.

[0191] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0192] Step 1: Weigh the above raw materials by mass;

[0193] Step 2: Weigh the nano-calcium carbonate and deionized water to prepare a 2% nano-calcium carbonate suspension by weight, and ultrasonically disperse for 30 minutes to obtain a suspension A;

[0194] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0195] Step 4: Evenly disperse the nano calcium carbonate suspension A in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2, pass argon, heat the mixture in a water bath to 45° C., and stir it with constant temperature magnetic force for 1 hour, add the weighed sodium humate, continue to stir it with constant temperature magnetic force for 3 hours, then cool the mixture to room temperature, filter, wash the filter cake with distilled water, dry it in a vacuum oven at 60° C. for 12 hours, and then grind it to obtain an organic nano calcium carbonate-sodium humate complex, recorded as complex D, and then add water to the complex D to prepare a suspension E with a weight percentage of 2%;

[0196] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0197] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0198] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0199] Step 8: slowly add the suspension E of the pre-obtained organic nano-calcium carbonate-sodium humate complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35°C, add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0200] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0201] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0202] Comparative Example 3

[0203] This comparative example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 12% nano calcium carbonate, 3% halloysite, 8% 3-aminopropyltriethoxysilane, 10% sodium carboxymethyl cellulose, 3% lambda carrageenan, 1% locust bean gum, 1% slaked lime, 30% first part N-hydroxymethyl acrylamide, 23% hydroxyethyl methacrylate, 8% methacrylic acid, 0.2% aluminum oxide, 0.3% second part N-hydroxymethyl acrylamide, and 0.5% ammonium sulfite.

[0204] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0205] Step 1: Weigh the above raw materials by mass;

[0206] Step 2: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse them for 30 minutes to obtain suspension A and suspension B;

[0207] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0208] Step 4: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed through, the mixed solution is heated to 45° C. in a water bath, and magnetically stirred at a constant temperature for 1 hour, then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, dried in a vacuum oven at 60° C. for 12 hours, and then ground to obtain an organic nano calcium carbonate and halloysite mixture, recorded as mixture D, and then the composite D is added with water to prepare a suspension E with a weight percentage of 2%;

[0209] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0210] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0211] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0212] Step 8: slowly add the suspension E of the pre-obtained mixture of organic nano-calcium carbonate and halloysite to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35° C., add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, stir at 450 r / min for 15 min, then add weighed ammonium sulfite, and continue stirring for 20 min to obtain a mixed solution H;

[0213] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0214] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0215] Comparative Example 4

[0216] The comparative example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 17% nano calcium carbonate, 3% halloysite, 10% sodium humate, 6% 3-aminopropyltriethoxysilane, 5% sodium carboxymethyl cellulose, 4% λ carrageenan, 2% locust bean gum, 1.2% slaked lime, 23% hydroxyethyl methacrylate, 27% methacrylic acid, 0.3% alumina, 0.5% N-hydroxymethyl acrylamide, and 1% ammonium sulfite.

[0217] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0218] Step 1: Weigh the above raw materials by mass;

[0219] Step 2: Weigh the nano-calcium carbonate, halloysite and deionized water to prepare a 2% nano-calcium carbonate suspension and a 1% halloysite suspension, respectively, and ultrasonically disperse them for 30 minutes to obtain suspension A and suspension B;

[0220] Step 3: The weighed 3-aminopropyltriethoxysilane is prepared into a dilute solution with a mass concentration of 3%, and then acetic acid is added to adjust the pH to 5.5-6, and magnetic stirring is performed for 30 minutes to obtain a 3-aminopropyltriethoxysilane hydrolyzate C;

[0221] Step 4: The nano calcium carbonate suspension A and the halloysite suspension B are uniformly dispersed in the 3-aminopropyltriethoxysilane hydrolyzate C in step 2 in sequence, argon is passed, the mixed solution is heated to 45° C. in a water bath, and magnetically stirred at a constant temperature for 1 hour, the weighed sodium humate is added, and the magnetic stirring at a constant temperature is continued for 3 hours, and then the mixed solution is cooled to room temperature, filtered, the filter cake is washed with distilled water, and dried in a vacuum oven at 60° C. for 12 hours and then ground to obtain an organic nano calcium carbonate-sodium humate-haloysite complex, which is recorded as complex D, and then water is added to the complex D to prepare a suspension E with a weight percentage of 2%;

[0222] Step 5: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0223] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed hydroxyethyl methacrylate while stirring continuously to fully dissolve to obtain a mixture G;

[0224] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0225] Step 8: slowly add the suspension E of the pre-obtained organic nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, pass nitrogen, stir at 300 r / min for 20 min in a constant temperature water bath at 35°C, add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence during continuous stirring, add weighed ammonium sulfite after stirring at 450 r / min for 15 min, and continue stirring for 20 min to obtain a mixed solution H;

[0226] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition, weighed alumina and N-hydroxymethyl acrylamide are added into a four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, a complex I is obtained.

[0227] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0228] Comparative Example 5

[0229] This comparative example provides a method for preparing a long-lasting salt-alkali resistant concrete curing material, which is composed of the following raw materials by weight: 10% sodium carboxymethyl cellulose, 4% λ carrageenan, 2% locust bean gum, 1.8% slaked lime, 49.4% first part N-hydroxymethyl acrylamide, 23% hydroxyethyl methacrylate, 8% methacrylic acid, 0.3% aluminum oxide, 0.5% second part N-hydroxymethyl acrylamide, and 1% ammonium sulfite.

[0230] The preparation method of the above-mentioned long-acting salt-alkali resistant concrete curing material comprises the following steps:

[0231] Step 1: Weigh the above raw materials by mass;

[0232] Step 2: slowly and evenly disperse the weighed λ carrageenan and locust bean gum in deionized water in turn, stir magnetically for 30 minutes, and prepare a dilute solution F with a concentration of 1%;

[0233] Step 6: Add methacrylic acid to deionized water to prepare a 15% dilute solution, add weighed slaked lime and cool to room temperature, add weighed first portions of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate while stirring continuously, and fully dissolve them to obtain a mixture G;

[0234] Step 7: Add the weighed sorbitan monostearate (Span 60) and cyclohexane into a four-necked flask, stir at 250 r / min for 30 min in a constant temperature water bath at 30° C. to 35° C. to form an oil phase;

[0235] Step 8: add weighed sodium carboxymethyl cellulose and pre-mixed λ carrageenan and locust bean gum dilute acid solution F in sequence, stir at 450 r / min for 15 min, then add weighed ammonium sulfite, and continue stirring for 20 min to obtain a mixed solution H;

[0236] Step 9: slowly drop the mixture G into the mixed solution H for 2 to 3 hours. After the dropwise addition is completed, weigh the aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added into the four-necked flask. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, the complex I is obtained.

[0237] Step 10: taking out the composite I, soaking and washing it with isopropanol for 3 to 5 times, and obtaining the long-lasting salt-alkali resistant concrete curing material after no more isopropanol evaporates.

[0238] Performance Testing

[0239] When using, directly add the long-term salt-alkali resistant concrete curing material together with cement and other cementitious materials into the mixing equipment for mixing, and refer to the requirements of JC901-2002 "Cement Concrete Curing Agent", JT / T522-2004 "Highway Engineering Concrete Curing Agent" and "Highway Engineering Cement and Cement Concrete Test Procedure" (JTG / E30-2005) to test the maximum liquid absorption rate of the curing material in saturated Ca(OH)2 solution and 0.9%wt CaCl2 solution, as well as the compressive strength ratio test and 28d shrinkage ratio (compared with the benchmark group) test of the concrete after addition. Among them, the dosage is 0.2% of the cementitious material dosage. The specific performance indicators are as follows:

[0240]

[0241]

[0242] It can be seen from the above embodiments that the long-term salt-alkali resistant concrete internal curing material water-retaining material can significantly improve the compressive strength of concrete. In the eight groups of examples, the maximum liquid absorption rate of the internal curing material water-retaining material in the saturated Ca(OH)2 solution is greater than 70g / g, and the maximum liquid absorption rate in the 0.9%wt CaCl2 solution is greater than 70g / g. Compared with the comparative example, the internal curing water-retaining material in the comparative example has a maximum liquid absorption rate of 0.9%wt CaCl2 solution in the saturated Ca(OH)2 solution. The maximum liquid absorption rate in the CaCl2 solution decreased significantly; and the 28d compressive strength of concrete in the eight groups of examples was more than 120% of that without internal curing materials, and the shrinkage ratio was less than 40%; compared with the comparative example, the strength of Example 28d was 7-20% higher than that of the comparative example, and the shrinkage ratio was 52% lower than that of the comparative example, which was significant, indicating that the lack of materials or the change in the proportion, especially the lack of organic nano calcium carbonate-sodium humate-halloysite composite (i.e., only retaining organic raw materials, the performance is similar to that of traditional organic internal curing materials), significantly affects the liquid absorption characteristics of the salt-alkali resistant internal curing water-retaining material in saline-alkali solution and the internal curing effect in concrete. Therefore, the salt-alkali resistant internal curing water-retaining material exhibits good liquid absorption characteristics in saline-alkali solution, and can play a good reinforcing role, and can also greatly reduce the self-shrinkage of concrete, and also has good applicability, can effectively solve the problems in the current concrete curing process in certain saline-alkali areas, and has broad application prospects.

[0243] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A long-term salt-alkali resistant concrete curing material, characterized in that: The invention is prepared from the following raw materials by weight: 12% to 17% of nano calcium carbonate, 3% to 5% of halloysite, 10% to 12% of sodium humate, 6% to 8% of 3-aminopropyltriethoxysilane, 5% to 10% of sodium carboxymethyl cellulose, 3% to 4% of lambda carrageenan, 1% to 2% of locust bean gum, 1% to 1.8% of slaked lime, 26% to 30% of the first part of N-hydroxymethyl acrylamide, 20% to 23% of hydroxyethyl methacrylate, 5% to 8% of methacrylic acid, 0.2% to 0.3% of aluminum oxide, 0.2% to 0.5% of the second part of N-hydroxymethyl acrylamide, and 0.5% to 1% of ammonium sulfite.

2. The long-acting salt-alkali resistant concrete curing material according to claim 1, characterized in that: The nano calcium carbonate has a particle size of 15 to 40 nm, a calcium carbonate content of ≥98.5, a pH of 8.5 to 10, and an impurity content of <0.1%; The particle diameter of halloysite is 0.1-0.4 μm, the length is less than 0.5 μm, and the purity is ≥99%; The particle diameter of the sodium humate is 120 meshes, the sodium humate content (dry basis) is ≥85%, the water-insoluble matter content is <5%, the pH is 9-11, and the moisture content is <12%.

3. The long-acting salt-alkali resistant concrete curing material according to claim 1, characterized in that: The sodium carboxymethyl cellulose is food grade, and the degree of substitution is ≥0.

9.

4. The long-lasting salt-alkali resistant concrete curing material according to claim 1, characterized in that: The nano calcium carbonate, halloysite, sodium humate and 3-aminopropyltriethoxysilane are used to prepare an organic nano calcium carbonate-sodium humate-haloysite composite; The organic nano calcium carbonate-sodium humate-halloysite composite is prepared by the following process: Nano-calcium carbonate and halloysite are mixed with deionized water to prepare nano-calcium carbonate suspension A with a weight percentage of 2% and halloysite suspension B with a weight percentage of 1% respectively; 3-aminopropyltriethoxysilane is prepared into a 3-aminopropyltriethoxysilane dilute solution with a mass concentration of 3%, and acetic acid is added to adjust the pH to obtain a 3-aminopropyltriethoxysilane hydrolyzate C; Nano calcium carbonate suspension A and halloysite suspension B are uniformly dispersed in 3-aminopropyltriethoxysilane hydrolyzate C in sequence, heated in a water bath, stirred, sodium humate is added, stirred continuously, cooled, filtered, washed, dried and ground to obtain an organic nano calcium carbonate-sodium humate-halloysite complex.

5. The long-acting salt-alkali resistant concrete curing material according to claim 4, characterized in that: The acetic acid adjusts the pH to 5.5-6.

6. A method for preparing the long-lasting salt-alkali resistant concrete curing material according to any one of claims 1 to 5, characterized in that: The following steps are involved: An organic nano calcium carbonate-sodium humate-halloysite composite was prepared by using nano calcium carbonate, halloysite, sodium humate and 3-aminopropyltriethoxysilane, which was recorded as composite D. Then, composite D was added with water to prepare suspension E. Dispersing λ carrageenan and locust bean gum in deionized water in sequence to prepare a dilute solution F; Add deionized water to methacrylic acid to prepare a dilute methacrylic acid solution, add slaked lime and cool to room temperature, and add the first portion of N-hydroxymethyl acrylamide and hydroxyethyl methacrylate during stirring to obtain a mixture G; Stirring sorbitan monostearate and cyclohexane in a constant temperature water bath to form an oil phase; Adding a suspension E of an organized nano-calcium carbonate-sodium humate-halloysite complex to the oil phase, stirring continuously, adding sodium carboxymethyl cellulose, λ-carrageenan and a dilute solution F of locust bean gum in sequence during stirring, and adding ammonium sulfite after a set time to obtain a mixed solution H; The mixture G is added dropwise to the mixed solution H, and after the addition is completed, aluminum oxide and a second portion of N-hydroxymethyl acrylamide are added to react to obtain a complex I; The composite I is taken out, soaked and cleaned to obtain the long-acting salt-alkali resistant concrete curing material.

7. The method for preparing the long-acting salt-alkali resistant concrete curing material according to claim 6, characterized in that: The weight percentage of the suspension E is 2%; the mass concentration of the dilute solution F is 1%; and the mass concentration of the dilute methacrylic acid solution is 15%.

8. The method for preparing the long-acting salt-alkali resistant concrete curing material according to claim 6, characterized in that: The sorbitan monostearate and cyclohexane are stirred at 250 r / min for 30 min in a constant temperature water bath environment of 30° C. to 35° C. to form an oil phase; The mass fraction of sorbitan monostearate is 5% to 7% of cyclohexane, and the volume ratio of the oil phase to the water phase is 4 to 4.5:

1.

9. The method for preparing the long-acting salt-alkali resistant concrete curing material according to claim 6, characterized in that: The specific process of preparing the mixed solution H is as follows: The suspension E of the organic nano-calcium carbonate-sodium humate-halloysite complex was slowly added to the oil phase, nitrogen was passed through, and the mixture was stirred at a speed of 300 r / min for 20 min in a constant temperature water bath environment of 35°C. During the continuous stirring process, the weighed sodium carboxymethyl cellulose and the pre-mixed λ-type carrageenan and locust bean gum dilute solution F were added in sequence, and the mixture was stirred at a speed of 450 r / min. After a setting time of 15 min, ammonium sulfite was added, and the mixture was stirred for 20 min to obtain a mixed solution H.

10. The method for preparing the long-acting salt-alkali resistant concrete curing material according to claim 6, characterized in that: The specific preparation process of the complex I is as follows: The mixture G is slowly added dropwise to the mixed solution H for 2 to 3 hours. After the addition is completed, aluminum oxide and the second portion of N-hydroxymethyl acrylamide are added. The temperature is controlled between 42°C and 45°C during the whole process. Argon is passed through. After reacting for 3 to 4 hours, complex I is obtained.

Citation Information

Patent Citations

  • Green moisture-preserving and slow-release composite organic cultivation substrate and preparation method of substrate

    CN111642359A

  • Foam concrete based on high-stability foaming agent and preparation method of foam concrete

    CN112279675A

  • Ternary polymerization saline-alkaline-tolerant slow-release water-absorbent resin with semi-interpenetrating network structure and application

    CN113248657A

  • Vegetation porous concrete and preparation method thereof

    CN117923941A

  • Calcium-alumino-silicate-hydrate nano-seeds suspension and preparation method thereof

    US20210276919A1